Visible-light active π-extended unsymmetrical squaraine dyes for dye-sensitized solar cells: steric effects for controlling the aggregation of dyes - Jadhav, Avinash P.; Siby, Jesna; Pandya, Rinu; Vanka, Kumar; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (ACS Applied Energy Materials, 2025)
The dye-anchored TiO2 photoanode plays a vital role in the light harvesting and charge separation processes in dye-sensitized solar cells. Aggregation of dyes (H- and J-type) on the TiO2 surface is a facile process due to the presence of a periodical dye anchoring sites on the exposed facet of titania, and such self-assembled dye structures help broadening the absorption profile. However, photocurrent generation from such aggregated structure is a challenging task in dye-sensitized solar cell devices. Hence, controlling the dye aggregation on the TiO2 surface is an important aspect. Controlling the aggregation of dyes by which (i) an enhanced photocurrent generation (J SC) and (ii) enhanced V OC can be achieved by including the steric factors to the dye design principles, the steric factor in the sensitizer may help passivate the TiO2 surface to avoid the charge recombination process between electrons present in TiO2 and the oxidized electrolyte. On the other hand, extension of pi-conjugation in a sensitizer helps enhance the light absorption in the visible region besides modulating the HOMO and LUMO energy levels. Hence, synergizing both pi-extensions along with features that control the dye aggregation has been considered in designing visible active squaraine dyes. A thiophene pi-spacer was inserted in between a visible-light active unsymmetrical squaraine unit and a cyanoacetic acid acceptor unit to provide the AJ1 and AJ2 dyes. Though both the dye molecules possess a similar pi-framework, the AJ2 dye was functionalized with both in-plane and out-of-plane alkyl groups to decrease the aggregation of dyes on the TiO2 surface compared to AJ1. The AJ1 and AJ2 dyes absorbed at 560 nm with shoulder peaks appeared at 528 nm, which can be assigned to vibronic progression (1082 cm-1), and additional characteristic peaks of thiophene appeared at 392 nm with the molar extinction coefficient of 1.16-1.19 x 105 M-1 cm-1 in CH3CN. The LUMO and HOMO energy levels are well aligned with the conduction band of TiO2 and the redox potential of iodolyte (I-/I3 -) electrolyte with sufficient overpotentials for charge injection and dye regeneration processes, respectively. The highest DSSC device efficiency of 7.37% (J SC 14.44 mA/cm2, V OC 0.771 V, ff 67.1%) was achieved for the AJ2 dye with iodolyte (I-/I3 -) electrolyte in the presence of 2 equiv of optically transparent coadsorbent chenodeoxycholic acid (CDCA), which showed a good IPCE response in between 400 and 700 nm. Further, cosensitization of visible-light active AJ1, AJ2, and SQA10 dyes with a complementary far-red active SQS4 dyes showed the device efficiencies of 5.53% (AJ1:SQS4:CDCA), 7.14% (AJ2:SQS4:CDCA), and 7.18% (SQA10:SQS4:CDCA) with a good IPCE response in the 400-720 nm region.
Keywords: cosensitization; Dye aggregation; Dye-sensitized solar cells; pi-extended squaraine dye; visible-lightactivedyes